Mechanical and Fracture Properties of Recycled Cellulose Fibre Reinforced Vinyl-ester Nanocomposites - Alhuthali, Abdullah; Low, It-Meng (Engineers Australia, 2010)
Compared to their synthetic counterparts, natural fibres are an environmentally friendly alternative demonstrating several attractive attributes including lower density, and lower cost. Vinyl-ester resin eco-composites reinforced with recycled cellulose fibre sheets (RCFs) have been fabricated in this study. Nanocomposites of vinyl-ester resin dispersed with nano-clay platelets was synthesized and studied. The mechanical properties, such as flexural strength, impact strength, impact toughness, and fracture toughness were evaluated. Porosities of all groups of samples have been investigated. Results indicated that strength properties decreased for nano-composites samples due to the poor dispersion of nanofiler and the existence of voids within the samples. In contrast, impact toughness and fracture toughness found to be improved for all RCFs reinforced samples. Finally, micro-structure of nano and eco-nanocomposites were investigated by scanning electron microscopy (SEM) with the results discussed.